(untitled) (Economic and Political Thought, 2013)
The article is an attempt to apply geo-economic analysis to assess the potential of the U.S. and the EU, and thus for the diagnosis of durability and power of the Euro-Atlantic security system. The author believes that the geo-economic analysis can determine the political and economic potential of both main parties to the Euro-Atlantic system, which have a decisive impact on the security and international world order changes.